Complete genome sequence of Actinosynnema mirum type strain (101T). Issue 1 (July 2009) - Land, Miriam; Lapidus, Alla; Mayilraj, Shanmugam; Chen, Feng; Copeland, Alex; Rio, Tijana; Nolan, Matt; Lucas, Susan; Tice, Hope; Cheng, Jan-Fang; Chertkov, Olga; Bruce, David; et al.
Abstract Actinosynnema mirum Hasegawaet al. 1978 is the type species of the genus, and is of phylogenetic interest because of its central phylogenetic location in theActinosynnemataceae, a rapidly growing family within the actinobacterial suborderPseudonocardineae .A. mirum is characterized by its motile spores borne on synnemata and as a producer of nocardicin antibiotics. It is capable of growing aerobically and under a moderate CO2 atmosphere. The strain is a Gram-positive, aerial and substrate mycelium producing bacterium, originally isolated from a grass blade collected from the Raritan River, New Jersey. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first complete genome sequence of a member of the familyActinosynnemataceae, and only the second sequence from the actinobacterial suborderPseudonocardineae . The 8, 248, 144 bp long single replicon genome with its 7100 protein-coding and 77 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.